Perspektif Peran Perempuan dalam Film Demi Nama Baik Kampus Analisis Wacana Kritis Model Sara Mills - Dita Isninadia; Achmad Yuhdi (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
This study examines the perspective of the role of women in the film "For the Good Name of the Campus" with the method of critical discourse analysis using the Sara Mills model. The research method used in this discussion is a qualitative descriptive method using Sara Mills' critical discourse analysis. Sara Mills takes a closer look at how the actors' positions appear in the text. Who positions himself as the narrator (subject) and who becomes the object being narrated, and sees how the position of the writer and the reader is positioned in the discourse. So, the research results reveal 5 scenes with subjects and objects.